Normative ultrasound data of the fetal transverse thalamic diameter derived from 18 to 22 weeks of gestation in routine second‐trimester morphology examinations. Issue 1 (19th January 2020) - Sridar, Pradeeba; Kennedy, Narelle J.; Quinton, Ann E.; Robledo, Kristy; Kim, Jinman; Nanan, Ralph
Abstract: Introduction: The thalamus is important for a wide range of sensorimotor and neuropsychiatric functions. Departure from normal reference values of the thalamus may be a biomarker for differences in neurodevelopment outcomes and brain anomalies perinatally. Antenatal measurement of thalamus is not currently included in routine fetal ultrasound as differentiation of thalamic borders is difficult. The aim of this work was to present a method to standardise the thalamus measure and provide normative data of the fetal transverse thalamic diameter between 18 and 22 weeks of gestational age. Methods: Transverse thalamic diameter was measured by two sonographers on 1, 111 stored ultrasound images at the standard transcerebellar plane. A 'guitar' shape representative structure is presented to demarcate the thalamic diameter. The relationship of the transverse thalamic diameter with gestational age, head circumference and transcerebellar diameter using linear regression modelling was assessed, and the mean of the thalamic diameter was calculated and plotted as a reference chart. Results: Transverse thalamic diameter increased significantly with increasing gestational age, head circumference, and transcerebellar diameter linearly, and normal range thalamic charts are presented. The guitar shape provided good reproducibility of thalamic diameter measures. Conclusion: Measuring thalamus size in antenatal ultrasound examinations with reference to normative charts could be used to assess midline brain structures and predict neurodevelopment disorders and potentially brain anomalies.